1997
DOI: 10.1007/s11589-997-0061-8
|View full text |Cite
|
Sign up to set email alerts
|

The influencing factors and mechanisms of the electromagnetic radiation during rock fracture

Abstract: Based on the laboratory experiments this paper presented that the primary influence factors about the electromagnetic radiation during rock fracture are the rock mechanics characters and mineral components. The brittle samples and samples contained quartz, pyrite, chalopyrite produce electromagnetic radiation easily. There are three fracture-radiation effects. The crystal fracture effect produces the high frequency electromagnetic signals, the piezoelectric effect produces low frequency signals and the natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Guo and Liu (1995) established an electric quadrupole model, calculated the frequency of the near electromagnetic field, and found that the frequency of the near electromagnetic field was related to the size of coal samples and the length of initial cracks and was about 50 kHz-1 MHz for granite samples with typical sizes and lengths of initial cracks. Liu et al (1997) experimentally found that rock during its rupture could produce EM signals of high frequency (1-5 MHz), intermediate frequency (100 kHz-1 MHz), and low frequency (100 Hz-100 kHz).…”
Section: List Of Symbols Xmentioning
confidence: 99%
“…Guo and Liu (1995) established an electric quadrupole model, calculated the frequency of the near electromagnetic field, and found that the frequency of the near electromagnetic field was related to the size of coal samples and the length of initial cracks and was about 50 kHz-1 MHz for granite samples with typical sizes and lengths of initial cracks. Liu et al (1997) experimentally found that rock during its rupture could produce EM signals of high frequency (1-5 MHz), intermediate frequency (100 kHz-1 MHz), and low frequency (100 Hz-100 kHz).…”
Section: List Of Symbols Xmentioning
confidence: 99%
“…(13), the solutions we derive include the ones given in Refs. [1][5], while when b i = 0, ours are all new solutions. In this sense we have extended the results obtained by Refs.…”
Section: Brief Formulation Of the New Methodsmentioning
confidence: 77%
“…In this sense we have extended the results obtained by Refs. [1][5]. Hence we are able to solve more nonlinear evolution equations and find more new solutions of the corresponding nonlinear evolution equations.…”
Section: Brief Formulation Of the New Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During coal and rock's deformation and failure, the dielectric constant increases and the emissivity decreases, thus leading to dropping MWR and its brightness temperature [25] . Moreover, the intensity of EMR generated by coal bursts will be changed if it meets natural semiconductor minerals, such as a majority of metal sulfides, so-called natural semiconductor property [26] . In the piezoelectric field, because there are natural similar semiconductor heterostructure to p-n-p or n-p-n junctions, as well as other heteromorphical conversion lock-off layers in some coal rock minerals, "active components", similar to transistor and silicon-controlled rectifiers and related to electrical circuits, are formed near their barriers.…”
Section: Dropping In Brightness Temperature Curvementioning
confidence: 99%